Synthetic method of antioxidant suitable for hydrophilic polyether, antioxidant and application of antioxidant
By synthesizing a new antioxidant in hydrophilic polyether, using highly active polyethers and 3,5-methyl ester for transesterification reaction, and catalyzed by lithium acetate, the turbidity problem that hydrophilic polyethers are prone to occur during processing is solved, and the good mutual solubility of antioxidant and polyethers and efficient anti-aging effects are achieved.
Patent Information
- Application Number
- CN202411599956.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-28
Smart Images

Figure CN119529263A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of antioxidant synthesis methods, and more specifically, to a synthesis method of an antioxidant suitable for hydrophilic polyether, an antioxidant and applications thereof. Background Art
[0002] Hydrophilic polyether polyol is a hydrophilic polymer, which is a high molecular compound formed by the polymerization reaction of alcohol and ether compounds. Hydrophilic polyether can not only form a stable dispersion system in water, used as emulsifier, dispersant and emulsifier to manufacture coatings, adhesives, leather treatment agents and other products; but also has good filling performance, plasticity and good bonding ability, and can provide excellent adhesion and durability in coatings and adhesives.
[0003] During the processing of hydrophilic polyether, the influence of temperature, light radiation, mechanical force and other factors may cause the molecular chain to break, resulting in the degradation of the performance of downstream products. Therefore, hydrophilic polyether manufacturers generally add a certain amount of antioxidants to improve the stability of the product.
[0004] Conventional antioxidants commonly used in polyethers include 1135, 1076, 5057, etc., which are all oil-soluble antioxidants. They will make the hydrophilic polyether turbid or the antioxidant precipitate from the polyether, and are not suitable for hydrophilic polyethers. Although emulsion-type compound antioxidants and hydrophilic polyethers are miscible, because the antioxidants are dissolved in water through surfactants to form an emulsion state, they cannot keep the hydrophilic polyether clear in appearance. Summary of the invention In order to reduce the turbidity problem of hydrophilic polyether, the present application provides a synthesis method of an antioxidant suitable for hydrophilic polyether, an antioxidant and application thereof.
[0006] In a first aspect, the present application provides a method for synthesizing an antioxidant suitable for hydrophilic polyethers, using the following technical solution: A method for synthesizing an antioxidant suitable for hydrophilic polyether comprises the following steps: S1, using high-activity polyether and 3,5-methyl ester as raw materials, under the catalysis of lithium acetate, heating and reducing pressure to obtain a crude product; S2, adding an adsorbent to the crude product, stirring, filtering and removing the filtrate to obtain; The hydroxyl value of the highly active polyether is 115 mgKOH·g -1 Within, the average molecular weight is 500.
[0007] By adopting the above technical solution: using polyether polyol and 3,5-methyl ester to undergo ester exchange reaction, inserting hindered phenol groups, combining antioxidant active structures and hydrophilic molecules through chemical reactions, so that it can have good mutual solubility with hydrophilic polyether. When the additive dosage is less than 0.5%, it can be well dissolved in hydrophilic polyether and keep the polyether in its original state, and it is not easy to become turbid. At the same time, high-activity polyether (referring to hydroxyl value of 115mgKOH·g -1 The polyether with an average molecular weight of 500 or less) replaces the current secondary hydroxy polyether, has high reaction activity, and the product has the characteristics of narrow molecular weight distribution, less volatile components, and low VOC, has higher precipitation resistance, and is beneficial to environmental protection.
[0008] Especially when lithium acetate is used for catalysis, compared with other catalysts, the detection turbidity point when added to the hydrophilic polyether is low, which further effectively reduces the turbidity problem, while other catalysts such as aluminum triisopropoxide, aluminum chloride, sodium acetate, potassium fluoride and the like cannot achieve this effect.
[0009] Optionally, the molecular weight of the antioxidant is 600-700.
[0010] Optionally, the dosage ratio of the high-activity polyether and 3,5-methyl ester is (2.3-2.7):1.
[0011] By adopting the above technical scheme: when the dosage of the high-activity polyether and 3,5-methyl ester is within the above range, the reaction is sufficient, the yield of the prepared antioxidant is high, and the hydrophilic polyether will not be easily turbid.
[0012] Optionally, the weight ratio of the added amount of lithium acetate to 3,5-methyl ester is (0.0025-0.0035):1.
[0013] Optionally, the specific steps of S1 are: Heat 3,5-methyl ester and highly active polyether, stir and dissolve, and keep warm at 130-140°C and vacuum 80-100mba for 30-60min; Break the vacuum, add lithium acetate, adjust the vacuum to 500-600mba, raise the temperature to 185-195℃ and react for 2-3h, collect and remove the by-product methanol, reduce the pressure in stages, remove 3,5-methyl ester, and obtain the crude product.
[0014] By adopting the above technical solution: adopting high temperature and low vacuum process conditions, it is more conducive to removing formaldehyde and promoting the positive reaction.
[0015] Optionally, the specific steps of the segmented decompression are: Stage 1: decompression to 95-105mba, maintain for 50-70min; Stage 2: Reduce pressure to 5-10mba and maintain for 30-60min; Stage three: full vacuum.
[0016] Optionally, the specific method of step S2 is: cooling the crude product to 85-90° C., adding an adsorbent, and stirring and mixing for 20-40 minutes.
[0017] Optionally, the adsorbent is one of magnesium silicate, aluminum silicate, diatomaceous earth, and activated carbon.
[0018] By adopting the above technical solution: the synthesis method of the present application has lower requirements on the adsorbent, and magnesium silicate, aluminum silicate, diatomaceous earth, and activated carbon can all be used in the process of the present application.
[0019] In a second aspect, the present application provides an antioxidant, which adopts the following technical solution: An antioxidant is prepared by the above-mentioned method for synthesizing an antioxidant suitable for hydrophilic polyether.
[0020] By adopting the above technical solution: the antioxidant prepared by the above synthesis method can be well dissolved in the hydrophilic polyether and keep the polyether in its original state without turbidity. At the same time, it has the characteristics of narrow molecular weight distribution, less volatile components, low VOC, higher precipitation resistance, and is beneficial to environmental protection.
[0021] In a third aspect, the present application provides an application of an antioxidant in a hydrophilic polyether, using the following technical solution: an application of an antioxidant in a hydrophilic polyether, wherein the concentration of the antioxidant is 1000-3000 PPM.
[0022] By adopting the above technical solution: when the dosage of the antioxidant is less than 0.5%, it can be well dissolved in the hydrophilic polyether and keep the polyether in its original state without turbidity. When the dosage is limited within the above range, it can play a good anti-aging role when it is processed downstream.
[0023] In summary, this application has the following beneficial effects: 1. The synthesis method of the present application uses a high-activity polyether with specific parameters and a specific catalyst for catalytic reaction. Compared with other antioxidants, it has better compatibility with hydrophilic polyethers, a high cloud point, is not easy to cause polyether turbidity, and has a high yield, which is conducive to the large-scale preparation of antioxidants; 2. The antioxidant of the present application has a low molecular weight. The lower the molecular weight of the antioxidant, the easier it is to cause turbidity in the polyether. The antioxidant of the present application can still ensure that the polyether has a higher turbidity point while maintaining a relatively low molecular weight; 3. The antioxidant of the present application has a good antioxidant effect and can well improve the antioxidant properties of the product within a concentration range of 1000-3000PPM. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a HPLC test chart of the antioxidant suitable for hydrophilic polyether in Example 1 of the present application; Figure 2 This is the HPLC detection chart of the antioxidant in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0025] The present application is further described in detail below in conjunction with embodiments.
[0026] Example 1 An antioxidant suitable for hydrophilic polyether, the structural formula of which is shown in the attached Figure 1 , and its synthesis method is: S1. Set the oil bath at 150°C, preheat the reaction bottle, add 80g 3,5-methyl ester, 200g high-activity polyether, set the vacuum at 80mba, start stirring after the raw materials are dissolved, and react for 45min at a temperature of 135°C and a vacuum of 90mba; break the vacuum, add 0.24g lithium acetate, react for 2.5h at a vacuum of 550mba and a temperature of 190°C (wherein methanol is collected and removed when the temperature rises to 180°C); reduce the pressure to 100mba, maintain for 60min, continue to reduce the pressure to 8mba, maintain for 45min, fully vacuum, remove 3,5-methyl ester, and obtain 274g crude product; S2. Cool the crude product to 85°C, add 4g of adsorbent (magnesium silicate), stir for 30min, filter and remove the filtrate while hot, and obtain an antioxidant suitable for hydrophilic polyether. The yield is 96.4%, the average molecular weight is 630, and the HPLC test chart is attached. Figure 2 .
[0027] The highly active polyether was obtained from Wanhua Chemical Group Co., Ltd., model wannol 1180; the hydroxyl value of the polyether is 115 mgKOH·g -1 , average molecular weight of 500, acid value of 0.05 mgKOH / g, moisture of 0.01%, viscosity of 60 mPa·s / 25°C.
[0028] Example 2 An antioxidant suitable for hydrophilic polyether, the synthesis method of which is: S1. Set the oil bath at 150°C, preheat the reaction bottle, add 80g 3,5-methyl ester and 200g high-activity polyether, set the vacuum at 80mba, start stirring after the raw materials are dissolved, and react for 60min at a temperature of 130°C and a vacuum of 80mba; break the vacuum, add 0.24g lithium acetate, and react for 3h at a vacuum of 500mba and a temperature of 185°C (wherein methanol is collected and removed when the temperature rises to 180°C); reduce the pressure to 95mba, maintain for 70min, continue to reduce the pressure to 5mba, maintain for 60min, fully vacuum, remove 3,5-methyl ester, and obtain a crude product; S2. Cool the crude product to 85° C., add 3 g of adsorbent (aluminum silicate), stir for 40 min, filter and remove the filtrate while hot to obtain an antioxidant with a yield of 94.6%.
[0029] The highly active polyether was obtained from Wanhua Chemical Group Co., Ltd., model wannol 1180; the hydroxyl value of the polyether is 115 mgKOH·g -1 , average molecular weight of 500, acid value of 0.05 mgKOH / g, moisture of 0.01%, viscosity of 60 mPa·s / 25°C.
[0030] Example 3 An antioxidant suitable for hydrophilic polyether, the synthesis method of which is: S1. Set the oil bath at 150°C, preheat the reaction bottle, add 80g 3,5-methyl ester and 200g highly active polyether, set the vacuum at 80mba, start stirring after the raw materials are dissolved, and react for 30min at a temperature of 140°C and a vacuum of 100mba; break the vacuum, add 0.24g lithium acetate, and react for 2h at a vacuum of 600mba and a temperature of 195°C (wherein methanol is collected and removed when the temperature rises to 180°C); reduce the pressure to 105mba, maintain for 50min, continue to reduce the pressure to 10mba, maintain for 30min, fully vacuum, remove 3,5-methyl ester, and obtain a crude product; S2. Cool the crude product to 90° C., add 5 g of adsorbent (magnesium silicate), stir for 20 min, filter and remove the filtrate while hot to obtain an antioxidant with a yield of 95.0%.
[0031] The highly active polyether was obtained from Wanhua Chemical Group Co., Ltd., model wannol 1180; the hydroxyl value of the polyether is 115 mgKOH·g -1 , average molecular weight of 500, acid value of 0.05 mgKOH / g, moisture of 0.01%, viscosity of 60 mPa·s / 25°C.
[0032] Example 4 An antioxidant suitable for hydrophilic polyether, which differs from Example 1 in that the amount of high-activity polyether in step S1 of the synthesis method is different, the amount ratio of high-activity polyether to 3,5-methyl ester is 2.3:1, and 268g of antioxidant is obtained, with a yield of 95.7%.
[0033] Example 5 An antioxidant suitable for hydrophilic polyether, which differs from Example 1 in that the amount of high-activity polyether in step S1 of the synthesis method is different, the amount ratio of high-activity polyether to 3,5-methyl ester is 2.7:1, and 264.8g of antioxidant is obtained, with a yield of 94.6%.
[0034] Example 6 An antioxidant suitable for hydrophilic polyether is different from Example 1 in that the amount of lithium acetate used in step S1 of the synthesis method is different, the amount ratio of lithium acetate to 3,5-methyl ester is 0.0025:1, and 266.8g of antioxidant is obtained with a yield of 95.3%.
[0035] Example 7 An antioxidant suitable for hydrophilic polyether, which is different from Example 1 in that the amount of lithium acetate used in step S1 of the synthesis method is different, the amount ratio of lithium acetate to 3,5-methyl ester is 0.0035:1, and 268g of antioxidant is obtained, with a yield of 95.7%.
[0036] Comparative Example 1 An antioxidant, which differs from Example 1 in that, in the synthesis process, an equal amount of polypropylene glycol 1000 is used to replace the high-activity polyether, and an equal amount of zinc chloride is used to replace lithium acetate.
[0037] The HPLC test of the obtained antioxidant is shown in the attached Figure 2 .
[0038] Comparative Example 2 An antioxidant is disclosed, which differs from Example 1 in that, in the synthesis process, an equal amount of aluminum triisopropoxide is used instead of lithium acetate, and 248 g of the antioxidant is obtained, with a yield of 88.7%.
[0039] Comparative Example 3 An antioxidant is disclosed, which is different from Example 1 in that, in the synthesis process, aluminum triisopropoxide is used as a catalyst instead of lithium acetate, and the amount of aluminum triisopropoxide used is 0.36 g, and 256 g of antioxidant is obtained, with a yield of 91.4%.
[0040] Comparative Example 4 An antioxidant, which differs from Example 1 in that an equal amount of aluminum chloride is used instead of lithium acetate in the synthesis process, and the yield is 96.0%.
[0041] Comparative Example 5 An antioxidant, which differs from Example 1 in that an equal amount of sodium acetate is used instead of lithium acetate in the synthesis process, and the yield is 96.6%.
[0042] Comparative Example 6 An antioxidant, which differs from Example 1 in that an equal amount of potassium fluoride is used instead of lithium acetate in the synthesis process, and the yield is 95.8%.
[0043] Performance Testing The antioxidants prepared in the examples and comparative examples were blended with polyether polyol 3000 and stirred uniformly, wherein the concentration of the antioxidant was 1000 PPM, to prepare samples, and another group of samples containing only polyether polyol and no antioxidant was set as a blank group. The samples were tested for the following properties, and the test results are recorded in Table 1.
[0044] Detection Methods 1. Cloud point: Tested according to method A in GB / T 5559-2010.
[0045] 2. Oxidation induction temperature: tested according to GB / T 19466.6-2009.
[0046] Table 1 Performance test results project Cloud point(℃) Oxidation induction temperature (℃) Example 1 80.5 179.1 Example 2 79.6 178.8 Example 3 78.7 178.4 Example 4 79.4 179.7 Example 5 79.8 179.5 Example 6 78.4 179.2 Example 7 79.1 178.6 Blank Group 81.0 155.7 Comparative Example 1 66.7 173.3 Comparative Example 2 68.9 174.6 Comparative Example 3 76.4 175.8 Comparative Example 4 75.2 175.9 Comparative Example 5 73.9 176.1 Comparative Example 6 74.4 176.3 Referring to the data in Table 1, by comparing Examples 1-3 and Comparative Example 1, it can be seen that the turbidity point of the prepared antioxidant using high-activity polyether and lithium acetate catalysis with specific parameters is as high as 80.5°C, which is not significantly lower than that of the blank group. In Comparative Example 1, a polyether with a molecular weight of 1000 is used instead of a high-activity polyether and other catalysts are used, and the turbidity point of the obtained antioxidant is only 66.7°C, indicating that the antioxidant of the present application does not significantly reduce the turbidity point and is not easy to cause turbidity of the polyether.
[0047] The difference between Comparative Examples 3-7 and Example 1 is that the use of catalysts is different. Comparative Example 2 uses aluminum triisopropoxide instead of lithium acetate, and the cloud point of the prepared antioxidant is reduced, and the yield is significantly reduced. Comparative Example 3 uses high-content aluminum triisopropoxide instead of lithium acetate, and the cloud point of the prepared antioxidant is reduced, and the yield is also reduced. Comparative Examples 4, 5, and 6 use the same amount of other catalysts, such as aluminum chloride, sodium acetate, and potassium fluoride instead of lithium acetate. The yield of some antioxidants is higher, but the cloud point is still low, which easily leads to turbidity of the polyether.
[0048] Application Example 1 The use of an antioxidant suitable for hydrophilic polyether in Example 1 comprises the following steps: blending the antioxidant of Example 1 with polyether polyol 3000, and stirring and mixing them uniformly. The concentration of the antioxidant is 2000 PPM; The oxidation induction temperature was tested and found to be 183.9°C.
[0049] Application Example 2 The use of an antioxidant suitable for hydrophilic polyether in Example 1 comprises the following steps: blending the antioxidant of Example 1 with polyether polyol 3000, and stirring and mixing them uniformly. The concentration of the antioxidant is 3000 PPM; The oxidation induction temperature test showed that the oxidation induction temperature was 184.5°C.
[0050] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for synthesizing an antioxidant suitable for hydrophilic polyether, characterized in that: The steps include: S1, using high-activity polyether and 3,5-methyl ester as raw materials, under the catalysis of lithium acetate, heating and reducing pressure to obtain a crude product; S2, adding an adsorbent to the crude product, stirring, filtering and removing the filtrate to obtain; The hydroxyl value of the highly active polyether is 115 mgKOH·g -1 Within, the average molecular weight is 500.
2. The method for synthesizing an antioxidant suitable for hydrophilic polyether according to claim 1, characterized in that: The molecular weight of the antioxidant is 600-700.
3. The method for synthesizing an antioxidant suitable for hydrophilic polyether according to claim 1, characterized in that: The dosage ratio of the high-activity polyether and 3,5-methyl ester is (2.3-2.7):
1.
4. The method for synthesizing an antioxidant suitable for hydrophilic polyether according to claim 1, characterized in that: The weight ratio of the added amount of lithium acetate to 3,5-methyl ester is (0.0025-0.0035):
1.
5. The method for synthesizing an antioxidant suitable for hydrophilic polyether according to claim 2, characterized in that: The specific steps of S1 are: Heat 3,5-methyl ester and highly active polyether, stir and dissolve, and keep warm at 130-140°C and vacuum 80-100mba for 30-60min; Break the vacuum, add lithium acetate, adjust the vacuum to 500-600mba, raise the temperature to 185-195℃ and react for 2-3h, collect and remove the by-product methanol, reduce the pressure in stages, remove 3,5-methyl ester, and obtain the crude product.
6. The method for synthesizing an antioxidant suitable for hydrophilic polyether according to claim 5, characterized in that: The specific steps of the segmented decompression are: Stage 1: decompression to 95-105mba, maintain for 50-70min; Stage 2: Reduce pressure to 5-10mba and maintain for 30-60min; Stage three: full vacuum.
7. The method for synthesizing an antioxidant suitable for hydrophilic polyether according to claim 1, characterized in that: The specific method of step S2 is: cooling the crude product to 85-90° C., adding an adsorbent, and stirring and mixing for 20-40 minutes.
8. The method for synthesizing an antioxidant suitable for hydrophilic polyether according to claim 7, characterized in that: The adsorbent is one of magnesium silicate, aluminum silicate, diatomaceous earth and activated carbon.
9. An antioxidant obtained by the synthesis method of an antioxidant suitable for hydrophilic polyether according to any one of claims 1 to 8.
10. Use of the antioxidant according to claim 9 in hydrophilic polyether, wherein the concentration of the antioxidant is 1000-3000 PPM.